Toxoplasma gondii seroprevalence studies on humans and animals in Africa - K. Hammond-Aryee; M. Esser; P.D. van Helden (South African Family Practice)
Background: Toxoplasmosis is a disease caused by Toxoplasma gondii, which can infect nearly all mammalian and avian species. Approximately 25% of the global human population is thought to be infected. Interest in toxoplasmosis has surged since it was discovered that with the onset of acquired immune deficiency syndrome, acute toxoplasmosis could induce cranial calcification. The ensuing encephalitis can be fatal. The African human immunodeficiency virus (HIV) epidemic, increasing levels of other immunosuppressive infections (such as tuberculosis), poor sanitation practices and lack of monitoring of at-risk populations point to a predicament that may be underrated.